ChemInform Abstract: Nickel‐Catalyzed Arylation of Heteroaryl‐Containing Diarylmethanes: Exceptional Reactivity of the Ni(NIXANTPHOS)‐Based Catalyst. Issue 17 (April 2016) - Cao, Xinyu; Sha, Sheng‐Chun; Li, Minyan; Kim, Byeong‐Seon; Morgan, Catherine; Huang, Rudan; Yang, Xiaodong; Walsh, Patrick J.
Abstract: In most cases, educts bearing one aryl and one pyridyl residue are used for the preparation of the desired triarylmethane products.